Broadband UV-to-green photoconversion in V-doped lithium zinc silicate glasses and glass ceramics - Gao, Guojun; Meszaros, Robert; Peng, Mingying; Wondraczek, Lothar (Optics Express, 2011)
We report on photoluminescence of vanadium-doped lithium zinc silicate glasses and corresponding nanocrystalline Li_2ZnSiO_4 glass ceramics as broadband UV-to-VIS photoconverters. Depending on dopant concentration and synthesis conditions, VIS photoemission from [VO4]3- is centered at 550-590 nm and occurs over a bandwidth (FWHM) of 250 nm. The corresponding excitation band covers the complete UV-B to UV-A spectral region. In as-melted glasses, the emission lifetime is about 34 extgreekms up to a nominal dopant concentration of 0.5 mol%. In the glass ceramic, it increases to about 45 extgreekms. For higher dopant concentration, a sharp drop in emission lifetime was observed, what is interpreted as a result of concentration quenching. Self-quenching is further promoted by energy transfer to V4+ centers (^2Гt4i̊ghtarrow^2Гt3). Partitioning of vanadium into V5+ and V4+ was examined by electron paramagnetic resonance and X-ray photoelectron spectroscopy. Suppression of V5+-reduction requires careful adjustment of the optical basicity of the host glass and/or synthesis conditions.
EAM Import::2019-03-13

Effect of thermal annealing on the mechanical properties of low-emissivity physical vapor deposited multilayer-coatings for architectural applications - Meszaros, Robert; Merle, Benoit; Wild, Michael; Durst, Karsten; Göken, Mathias; Wondraczek, Lothar (Thin Solid Films, 2012)
Low-emissivity (low-E) coatings comprising a stack of multiple physical vapor deposited metallic and dielectric layers play an important role in energy management of modern buildings. The production process of such architectural glazings often requires that the coatings withstand a short-term thermal load of up to 700 °C. Here, we report on thermally-induced variations in the mechanical properties of representative large-area magnetron-sputtered low-E stacks on glass, developed specifically for high temperature stability. Coatings are investigated before and after heat treatment by bulge testing, curvature analyses using Stoney's equation, and nanoindentation. For as-deposited coatings, an in-plane residual compressive stress about 48 MPa and Young's modulus of 120 GPa are found, depending on the type of substrate. Short-term exposure to up to 700 °C converts this situation to in-plane residual tensile stress of > 400 MPa, while Young's modulus decreases to about 105 GPa. These changes in the residual stress state are explained on the basis of structural, topological and dimensional changes in the coating stack. They identified as one of the primary factors governing temperature-resistance of low-E coatings.
WW1::923

Flexural strength of PVD coated float glass for architectural applications - Meszaros, Robert; Wild, Michael; Merle, Benoit; Wondraczek, Lothar (Glass Technology-European Journal of Glass Science and Technology Part A, 2011)
The effect of PVD coatings on the ring-on-ring flexural strength of soda lime silica float glass was studied. A 70% increase from 280 +/- 8 to 478 +/- 10 MPa was observed on the air-side of the glass after applying a multilayer low emissivity coating of 100 nm total thickness. A similar but less pronounced effect could be obtained with a TiO(2) single layer of 50 nm. At the same time, for both coatings, the Weibull modulus was found to approximately double. Results are interpreted on the basis of two assumptions: initial defects on the glass surface are covered by the coating, and their growth is prevented due to the protective function of the coating, especially as a humidity barrier. Both assumptions were confirmed by atomic force microscopy and micromechanical analyses. This barrier function leads to significantly improved resistance to long term fatigue and stress corrosion, respectively.

In vitro reactivity of Cu doped 45S5 Bioglass® derived scaffolds for bone tissue engineering - Hoppe, Alexander; Meszaros, Robert; Staehli, Christoph; Romeis, Stefan; Schmidt, Jochen; Peukert, Wolfgang; Marelli, Benedetto; Nazhat, Showan N.; Wondraczek, Lothar; Lao, Jonathan; Jallot, Edouard; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2013)
Cu-doped 45S5 bioactive glasses with varying Cu contents were fabricated and used to process 3D porous scaffolds via the foam replica technique. Cu-doping results in the weakening of the glass network and a decrease in its glass transition temperature. Acellular in vitro studies revealed very high bioactivity independent of Cu doping as indicated by the fast formation of a carbonated hydroxyapatite layer (CHA) on scaffold surfaces after immersion in simulated body fluid (SBF). The kinetics of the glass-ceramic scaffold's transition to an amorphous calcium phosphate layer (ACP) and the crystallisation of CHA were explored by FT-IR and SEM analyses. The elemental distribution in the scaffold/fluid interface region was monitored by the advanced micro-PIXE-RBS (particle induced X-ray emission/Rutherford backscattering spectrometry) method. Cu-containing glasses showed slower release of Si, Ca and P from the scaffold periphery, whereas traces of Cu were found incorporated in the CaP layer on the scaffold surface. Cu release kinetics from the scaffolds in SBF were found to depend on culturing conditions while highest Cu concentrations of ∼3.1 ppm and ∼4.6 ppm under static and quasi-dynamic conditions, respectively, were observed. Since Cu exhibits potential angiogenic and osteogenic properties, the Cu-containing scaffolds are suggested as promising materials for bone tissue engineering applications. © 2013 The Royal Society of Chemistry.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.invitr_2

Sintering of 3D-Printed Glass/HAp Composites - Winkel, Alexander; Meszaros, Robert; Reinsch, Stefan; Mueller, Ralf; Travitzky, Nahum; Fey, Tobias; Greil, Peter; Wondraczek, Lothar (Journal of the American Ceramic Society, 2012)
We report the sintering of 3D-printed composites of 13-93 bioactive glass and hydroxyapatite (HAp) powders. The sintering process is characterized on conventionally produced powder compacts with varying HAp content. A numeric approximation of the densification kinetics is then obtained on the basis of Frenkel, Mackenzie-Shuttleworth, and Einstein-Roscoe models, and optimized sintering conditions for 3D-printed structures are derived. Fully isotropic sintering of complex cellular composites is obtained by continuous heating to 750 degrees C at a rate of 2 K/min for a HAp content of 40 wt%. The approach can readily be generalized for printing and sintering of similar glass-ceramic composites.

Three-dimensional printing of a bioactive glass - Meszaros, Robert; Zhao, Rong; Travitzky, Nahum; Fey, Tobias; Greil, Peter; Wondraczek, Lothar (Glass Technology-European Journal of Glass Science and Technology Part A, 2011)
We report on three-dimensional printing and subsequent sintering of 13-93 bioactive glass as a powerful method for the fabrication of patient-specific inlays and substitutes for unloaded implants. In a multi-method study, an assessment of thermal sintering, isotropic and anisotropic shrinkage, crystallisation and microstructural evolution was performed as a prerequisite for the development of a suitable 3D-printing and sintering process. Concave and convex model geometries were then produced, and their consolidation behaviour was examined with respect to process parameters such as adequate preparation of precursor glass powders, particle size used, glass viscosity, green body preparation and sintering conditions. Almost complete densification could be achieved for sintering temperatures of 742-795 degrees C. Crystallisation was observed to involve subsequent precipitation of diopside (similar to 750 degrees C), parawollastonite (similar to 850 degrees C) and calcium phosphate (similar to 900 degrees C). A process window of 712-745 degrees C reducing to 712-730 degrees C, if crystallisation must be avoided, is suggested for sintering of 3D printed bioactive glass type 13-93.